High-strength and flame-retardant PVC drag chain cable material and preparation method thereof

By preparing high-strength and flame-retardant PVC drag chain cable material and combining with special processes, the existing materials have been solved inadequate performance in high-twist and low-temperature environments, and excellent resistance to twist, oil and flame retardant performance is achieved. It is suitable for the third-generation intelligent drag chain electric robot.

CN119912766APending Publication Date: 2025-05-02苏州盈创特种材料有限公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510212884.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-26
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing drag chain cable materials lack sufficient performance in high twist and low temperature environments, making it difficult to meet the high requirements of the third-generation intelligent drag chain electrical robots for flexibility and durability.

Method used

High-strength and flame-retardant PVC drag chain cable material is used to prepare cable materials with excellent anti-twist, oil and flame-retardant properties by preparing A and B PVC resins, polyester plasticizers, nitrile rubbers, copolymers and other materials, combined with special processes such as mixing, extrusion, refining, granulation and screening.

Benefits of technology

It achieves high strength and flame retardant properties without cracking in an environment of minus 50℃, meets the aging requirements of 158℃ for 10 days, and passes the oil resistance test of German standard TM5 sheath and the CM grade verification in the UL flame retardant experiment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912766A_ABST
    Figure CN119912766A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of environment-friendly cable materials, and particularly relates to a high-strength and flame-retardant PVC drag chain cable material and a preparation method thereof. The PVC drag chain cable material is prepared from A type PVC resin, B type PVC resin, trioctyl trimellitate, a 2050 polyester plasticizer, antimony trioxide, zinc borate, filler, aluminum hydroxide, a calcium-zinc heat stabilizer, P95 nitrile rubber, an ethylene-vinyl acetate copolymer, a lubricant, a P551J processing modifier, an ethylene-vinyl acetate-maleic anhydride copolymer, a polyester elastomer and inorganic silicate clay. The PVC drag chain cable material designed by the invention has excellent low temperature resistance, can be used in a working environment of-50 DEG C without cracking after being made into a cable, also has the properties of high electrical property, high oil resistance, torque resistance and the like, and is suitable for industrial popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmentally friendly cable materials, and in particular relates to a high-strength and flame-retardant PVC drag chain cable material and a preparation method thereof. Background Art

[0002] The link wires used in drag chain cables, as the "meridians" of artificial robots, are gradually changing the requirements of traditional wires and cables with the development of drag chain cables. From the previous requirement of only meeting the conventional physical properties, the requirements of winding resistance, twisting resistance, oil resistance, etc. have been added. Today's third-generation intelligent drag chain cable robots have proposed flexible development. The robot's working range has been expanded, and the flexibility of work has been improved compared with before. It is not only the original mechanical two-dimensional work, but now the robot arm is required to automatically flip 360 degrees or more, which will inevitably require the power line to have good anti-twisting performance, otherwise the wire will easily crack.

[0003] Because of the torsion resistance requirements of drag chain cables, TPE or TPU elastomers are generally used as insulation and sheaths in the market. Such materials have good torsion resistance and certain oil resistance, but are relatively expensive.

[0004] Therefore, how to solve the above-mentioned deficiencies in the prior art has become a subject to be studied and solved by the present invention.

[0005] Therefore, the present invention proposes a high-strength and flame-retardant PVC drag chain cable material and a preparation method thereof. The cable material has low cost, excellent anti-twisting performance and good low-temperature resistance. After being made into a cable, it can be used in a working environment of minus 50°C without cracking. PVC elastic material is used to replace TPE or TPU material. The prepared cable material also has high electrical properties, high oil resistance, anti-torque and other properties, and is suitable for industrial promotion. Summary of the invention

[0006] The present invention aims to provide a high-strength and flame-retardant PVC drag chain cable material and a preparation method thereof. By improving relevant processes and raw materials, the anti-twisting performance, high and low temperature performance, oil resistance, torque resistance and other properties of the PVC drag chain cable are improved.

[0007] The specific implementation scheme of a high-strength and flame-retardant PVC drag chain cable material and a preparation method thereof according to the present invention is as follows:

[0008] A high-strength and flame-retardant PVC drag chain cable material raw material includes type A PVC resin, type B PVC resin, trioctyl trimellitate, 2050 polyester plasticizer, antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, P95 nitrile rubber, ethylene-vinyl acetate copolymer, lubricant, P551J processing modifier, ethylene-vinyl acetate-maleic anhydride copolymer, polyester elastomer, and inorganic silicate clay;

[0009] The dosage is measured by mass, including: 50-100 parts of type A PVC resin, 10-50 parts of type B PVC resin, 10-20 parts of trioctyl trimellitate, 15-20 parts of 2050 polyester plasticizer, 4-8 parts of antimony trioxide, 6-10 parts of zinc borate, 4-8 parts of filler, 8-16 parts of aluminum hydroxide, 8-12 parts of calcium zinc heat stabilizer, 10-15 parts of P95 nitrile rubber, 10-15 parts of ethylene-vinyl acetate copolymer, 0.4-0.6 parts of lubricant, 0.4-1 parts of P551J processing modifier, 3-5 parts of ethylene-vinyl acetate-maleic anhydride copolymer, 10-20 parts of polyester elastomer, and 1-2 parts of inorganic silicate clay;

[0010] The polymerization degree of the type A PVC resin is 1000-1500;

[0011] The B-type PVC resin has a degree of polymerization of 2000-3000;

[0012] The vinyl acetate content in the ethylene-vinyl acetate copolymer is 25-35%;

[0013] The filler is selected from at least one of calcium carbonate, talc and kaolin;

[0014] The lubricant is selected from at least one of stearic acid, polyethylene wax, calcium stearate, and zinc stearate;

[0015] The ethylene-vinyl acetate-maleic anhydride copolymer is prepared by the following steps:

[0016] Step 1: Place ethylene-vinyl acetate copolymer and maleic anhydride into a high-speed mixer and stir for 20-40 minutes to mix thoroughly;

[0017] Step 2: Put the mixed ethylene-vinyl acetate copolymer and maleic anhydride into the barrel of a twin-screw extruder for extrusion process at an extrusion temperature of 140-160°C, and add an initiator in the third heating zone;

[0018] The initiator content is 0.5-1 part, and the mixture is prepared by mixing dicumyl peroxide, 2,5-dimethyl-2,5-bishexane and antioxidant 1010 in a mass ratio of 1:0.8-1.2:0.8-1.2, and the mixing method is ball milling stirring, the speed is 200-300rpm, and the time is 30-60min;

[0019] Step 3: Use a single screw granulator to granulate, and set the granulation temperature to 90-110℃;

[0020] Step 4: cooling and sieving to obtain the ethylene-vinyl acetate-maleic anhydride copolymer, wherein the particle size of the sieved material is 0.5-0.8 mm;

[0021] A preparation method of a high-strength and flame-retardant PVC drag chain cable material comprises the steps of mixing, extrusion, refining, granulation, screening, etc. The specific implementation process is as follows:

[0022] The preparation process of the mixed material is as follows:

[0023] Step 1: Add 5-10 parts of type B PVC resin and trimellitate into a high-speed mixer and pre-mix for 2-5 minutes at room temperature, then mix at high speed for 3-7 minutes.

[0024] Step 2: Add type A PVC resin, 2050 polyester plasticizer and the remaining trimellitate into a high-speed mixer and mix for 3-7 minutes, and turn on the heating at the same time. When the heating temperature reaches 100-120℃, mix at a low speed for 1-3 minutes.

[0025] Step 3: Add antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, lubricant, inorganic silicate clay, and P551J processing modifier into a high-speed mixer and mix at high speed for 3-7 minutes.

[0026] Step 4: Add ethylene-vinyl acetate-maleic anhydride copolymer, P95 nitrile rubber, ethylene-vinyl acetate copolymer and polyester elastomer into a high-speed mixer, mix at a low speed for 1-3 minutes to obtain a mixture, and the mixing temperature is 130-140°C;

[0027] The extrusion preparation process is as follows:

[0028] The mixed material is added into a twin-screw extruder for extrusion to obtain an extrudate, the extrusion temperature is set at 130-150°C, and the screw speed frequency is 30-50Hz;

[0029] The preparation process of the open refining is as follows:

[0030] The extrudate is added into an open mill for open milling to obtain an open mill material, and the open milling temperature is set at 160-180° C. The granulation preparation process is as follows:

[0031] The raw material is added into a single screw granulator for granulation to obtain granulated material, and the granulation temperature is set at 80-110°C;

[0032] The preparation process of the sieving is as follows:

[0033] The granulated material is cooled and then sieved, and the particle size of the sieved material is 2-5 mm, so that the high-strength and flame-retardant PVC drag chain cable material is obtained.

[0034] Beneficial effects:

[0035] (1) The soft high-strength flame-retardant PVC cable material for the drag chain cable of the present invention adopts PVC resin with a polymerization degree of 1300, PVC resin with a polymerization degree of 2500, trimellitate, 2050 polyester plasticizer, antimony trioxide, zinc borate, filler, aluminum hydroxide, and calcium zinc heat stabilizer, and further adds polyester elastomer, ethylene-vinyl acetate-maleic anhydride copolymer, P95 nitrile rubber, ethylene-vinyl acetate copolymer and inorganic silicate clay. The prepared cable material can meet the aging requirement of 158° C. for 10 days under the premise of maintaining the Shore hardness at 80HA. In the low-temperature embrittlement test at -40° C., the low-temperature performance of the product enables the product to be used in a working environment of -50° C. without cracking after being made into a cable;

[0036] (2) The addition of 2050 polyester plasticizer, ethylene-vinyl acetate copolymer and nitrile rubber P95 of the present invention also effectively improves the oil resistance of the product, meeting the oil resistance aging standard of 168 hours at 90° C. required by the German standard TM5 sheath. The use of 1 to 2 parts of inorganic silicate clay improves the flame retardant performance and shell forming effect of the product, reaching the CM grade in the UL flame retardant test.

[0037] (3) The soft, high-strength, flame-retardant PVC cable material for the drag chain cable of the present invention is a PVC resin whose formula further adds a polyester elastomer and an ethylene-vinyl acetate-maleic anhydride copolymer, which is blended with the PVC material, thereby overcoming the disadvantage of poor compatibility between PVC and TPEE. The PVC material has the characteristics of easy molding, good resilience and good wear resistance of the TPEE material, and has excellent anti-twisting performance, and can achieve U-shaped reciprocating bending for more than 20 million times and rotation of 270° for more than 10 million times without cracking;

[0038] (4) In the preparation process of the ethylene-vinyl acetate-maleic anhydride copolymer of the present invention, dicumyl peroxide, 2,5-dimethyl-2,5-bishexane and antioxidant 1010 compounded in a weight ratio of 1:1:1 are used as initiators, and the grafting rate reaches 1.6wt%, the elongation reaches more than 800%, and it is not easy to yellow, which can effectively improve the compatibility of the system and enhance the tensile and impact strength of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The present invention is a preparation flow chart of a high-strength and flame-retardant PVC drag chain cable material and a preparation method thereof. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0041] Embodiment 1:

[0042] A high-strength and flame-retardant PVC drag chain cable material raw material includes type A PVC resin, type B PVC resin, trioctyl trimellitate, 2050 polyester plasticizer, antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, P95 nitrile rubber, ethylene-vinyl acetate copolymer, lubricant, P551J processing modifier, ethylene-vinyl acetate-maleic anhydride copolymer, polyester elastomer, and inorganic silicate clay;

[0043] The dosage is measured by mass, including: 50 parts of type A PVC resin, 10 parts of type B PVC resin, 10 parts of trioctyl trimellitate, 15 parts of 2050 polyester plasticizer, 4 parts of antimony trioxide, 6 parts of zinc borate, 4 parts of filler, 8 parts of aluminum hydroxide, 8 parts of calcium zinc heat stabilizer, 10 parts of P95 nitrile rubber, 10 parts of ethylene-vinyl acetate copolymer, 0.4 parts of lubricant, 0.4 parts of P551J processing modifier, 3 parts of ethylene-vinyl acetate-maleic anhydride copolymer, 10 parts of polyester elastomer, and 1 part of inorganic silicate clay;

[0044] The degree of polymerization of the type A PVC resin is 1000;

[0045] The B-type PVC resin has a degree of polymerization of 2000;

[0046] The vinyl acetate content in the ethylene-vinyl acetate copolymer is 25%;

[0047] The filler is selected from talc;

[0048] The lubricant is selected from stearic acid;

[0049] The ethylene-vinyl acetate-maleic anhydride copolymer is prepared by the following steps:

[0050] Step 1: Put ethylene-vinyl acetate copolymer and maleic anhydride into a high-speed mixer and stir for 20 minutes to mix them thoroughly;

[0051] Step 2: Put the mixed ethylene-vinyl acetate copolymer and maleic anhydride into the barrel of a twin-screw extruder for extrusion process at an extrusion temperature of 140°C, and add an initiator in the third heating zone;

[0052] The initiator content is 0.5 parts, and is prepared by mixing diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bishexane and antioxidant 1010 in a mass ratio of 1:0.:0.8, and the mixing method is ball milling stirring, the speed is 200 rpm, and the time is 30 minutes;

[0053] Step 3: Granulate with a single screw granulator, and set the granulation temperature to 90°C;

[0054] Step 4: cooling and sieving to obtain the ethylene-vinyl acetate-maleic anhydride copolymer, wherein the particle size of the sieved material is 0.5 mm;

[0055] A preparation method of a high-strength and flame-retardant PVC drag chain cable material comprises the steps of mixing, extrusion, refining, granulation, screening, etc. The specific implementation process is as follows:

[0056] The preparation process of the mixed material is as follows:

[0057] Step 1: Add 5 parts of type B PVC resin and trimellitate into a high-speed mixer and stir for premixing at room temperature for 2 minutes, then mix at high speed for 3 minutes.

[0058] Step 2: Add type A PVC resin, 2050 polyester plasticizer and the remaining trimellitate into a high-speed mixer and mix for 3 minutes, and turn on the heating at the same time. When the heating temperature reaches 100°C, mix at a low speed for 1 minute.

[0059] Step 3: Add antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, lubricant, inorganic silicate clay, and P551J processing modifier into a high-speed mixer and mix at high speed for 3 minutes.

[0060] Step 4: Add ethylene-vinyl acetate-maleic anhydride copolymer, P95 nitrile rubber, ethylene-vinyl acetate copolymer and polyester elastomer into a high-speed mixer, mix at a low speed for 1 minute to obtain a mixture, and the mixing temperature is 130°C;

[0061] The extrusion preparation process is as follows:

[0062] The mixed material is added into a twin-screw extruder for extrusion to obtain an extrudate, the extrusion temperature is set at 130°C, and the screw speed frequency is 30 Hz;

[0063] The preparation process of the open refining is as follows:

[0064] The extrudate is added into an open mill for open milling to obtain an open mill material, and the open milling temperature is set to 160° C. The granulation preparation process is as follows:

[0065] The raw material was added into a single screw granulator for granulation to obtain granulated material, and the granulation temperature was set at 80°C;

[0066] The preparation process of the sieving is as follows:

[0067] The granulated material is cooled and then sieved, and the particle size of the sieved material is 2 mm, thus obtaining the high-strength and flame-retardant PVC drag chain cable material.

[0068] Embodiment 2:

[0069] A high-strength and flame-retardant PVC drag chain cable material raw material includes type A PVC resin, type B PVC resin, trioctyl trimellitate, 2050 polyester plasticizer, antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, P95 nitrile rubber, ethylene-vinyl acetate copolymer, lubricant, P551J processing modifier, ethylene-vinyl acetate-maleic anhydride copolymer, polyester elastomer, and inorganic silicate clay;

[0070] The dosage is measured by mass, including: 100 parts of type A PVC resin, 50 parts of type B PVC resin, 20 parts of trioctyl trimellitate, 20 parts of 2050 polyester plasticizer, 8 parts of antimony trioxide, 10 parts of zinc borate, 8 parts of filler, 16 parts of aluminum hydroxide, 12 parts of calcium zinc heat stabilizer, 15 parts of P95 nitrile rubber, 15 parts of ethylene-vinyl acetate copolymer, 0.6 parts of lubricant, 1 part of P551J processing modifier, 5 parts of ethylene-vinyl acetate-maleic anhydride copolymer, 20 parts of polyester elastomer, and 2 parts of inorganic silicate clay;

[0071] The polymerization degree of the type A PVC resin is 1500;

[0072] The B-type PVC resin has a degree of polymerization of -3000;

[0073] The vinyl acetate content in the ethylene-vinyl acetate copolymer is 35%;

[0074] The filler is selected from talc;

[0075] The lubricant is selected from stearic acid;

[0076] The ethylene-vinyl acetate-maleic anhydride copolymer is prepared by the following steps:

[0077] Step 1: Put ethylene-vinyl acetate copolymer and maleic anhydride into a high-speed mixer, stir for 40 minutes, and mix thoroughly;

[0078] Step 2: Put the mixed ethylene-vinyl acetate copolymer and maleic anhydride into the barrel of a twin-screw extruder for extrusion process at an extrusion temperature of 160°C, and add an initiator in the third heating zone;

[0079] The initiator content is 1 part, and is prepared by mixing diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bishexane and antioxidant 1010 in a mass ratio of 1:1.2:1.2, and the mixing method is ball milling stirring, the speed is 300 rpm, and the time is 60 minutes;

[0080] Step 3: Granulate with a single screw granulator, and set the granulation temperature to 110°C;

[0081] Step 4: cooling and sieving to obtain the ethylene-vinyl acetate-maleic anhydride copolymer, the particle size of the sieve material is 0.8 mm;

[0082] A preparation method of a high-strength and flame-retardant PVC drag chain cable material comprises the steps of mixing, extrusion, refining, granulation, screening, etc. The specific implementation process is as follows:

[0083] The preparation process of the mixed material is as follows:

[0084] Step 1: Add 10 parts of type B PVC resin and trimellitate into a high-speed mixer and stir for premixing at room temperature for 5 minutes, then mix at high speed for 7 minutes.

[0085] Step 2: Add type A PVC resin, 2050 polyester plasticizer and the remaining trimellitate into a high-speed mixer and mix for 7 minutes, and turn on the heating at the same time. When the heating temperature reaches 120°C, mix at a low speed for 3 minutes.

[0086] Step 3: Add antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, lubricant, inorganic silicate clay, and P551J processing modifier into a high-speed mixer and mix at high speed for 7 minutes.

[0087] Step 4: Add ethylene-vinyl acetate-maleic anhydride copolymer, P95 nitrile rubber, ethylene-vinyl acetate copolymer and polyester elastomer into a high-speed mixer, mix at a low speed for 3 minutes to obtain a mixture, and the mixing temperature is 140°C;

[0088] The extrusion preparation process is as follows:

[0089] The mixed material is added into a twin-screw extruder for extrusion to obtain an extrudate, the extrusion temperature is set at 150°C, and the screw speed frequency is 50 Hz;

[0090] The preparation process of the open refining is as follows:

[0091] The extrudate is added into an open mill for open milling to obtain an open mill material, and the open milling temperature is set to 180° C. The granulation preparation process is as follows:

[0092] The raw material was added into a single screw pelletizer for pelletizing to obtain pelletized material, and the pelletizing temperature was set at 110°C;

[0093] The preparation process of the sieving is as follows:

[0094] The granulated material is cooled and then sieved, and the particle size of the sieved material is 5 mm, so that the high-strength and flame-retardant PVC drag chain cable material is obtained.

[0095] Embodiment 3:

[0096] A high-strength and flame-retardant PVC drag chain cable material raw material includes type A PVC resin, type B PVC resin, trioctyl trimellitate, 2050 polyester plasticizer, antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, P95 nitrile rubber, ethylene-vinyl acetate copolymer, lubricant, P551J processing modifier, ethylene-vinyl acetate-maleic anhydride copolymer, polyester elastomer, and inorganic silicate clay;

[0097] The dosage is measured by mass, including: 80 parts of type A PVC resin, 30 parts of type B PVC resin, 15 parts of trioctyl trimellitate, 17 parts of 2050 polyester plasticizer, 6 parts of antimony trioxide, 8 parts of zinc borate, 4-8 parts of filler, 12 parts of aluminum hydroxide, 10 parts of calcium zinc heat stabilizer, 13 parts of P95 nitrile rubber, 12 parts of ethylene-vinyl acetate copolymer, 0.5 parts of lubricant, 0.8 parts of P551J processing modifier, 4 parts of ethylene-vinyl acetate-maleic anhydride copolymer, 15 parts of polyester elastomer, and 1.5 parts of inorganic silicate clay;

[0098] The polymerization degree of the type A PVC resin is 1200;

[0099] The B-type PVC resin has a degree of polymerization of 2500;

[0100] The vinyl acetate content in the ethylene-vinyl acetate copolymer is 30%;

[0101] The filler is selected from at least one of calcium carbonate, talc and kaolin;

[0102] The lubricant is selected from at least one of stearic acid, polyethylene wax, calcium stearate, and zinc stearate;

[0103] The ethylene-vinyl acetate-maleic anhydride copolymer is prepared by the following steps:

[0104] Step 1: Put ethylene-vinyl acetate copolymer and maleic anhydride into a high-speed mixer and stir for 30 minutes to mix them thoroughly;

[0105] Step 2: Put the mixed ethylene-vinyl acetate copolymer and maleic anhydride into the barrel of a twin-screw extruder for extrusion process at a temperature of 150°C, and add an initiator in the third heating zone;

[0106] The initiator content is 0.8 parts, and is prepared by mixing diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bishexane and antioxidant 1010 in a mass ratio of 1:1:1, and the mixing method is ball milling stirring, the speed is 250 rpm, and the time is 40 minutes;

[0107] Step 3: Granulate with a single screw granulator, and set the granulation temperature to 100°C;

[0108] Step 4: cooling and sieving to obtain the ethylene-vinyl acetate-maleic anhydride copolymer, the particle size of the sieved material is 0.6 mm;

[0109] A preparation method of a high-strength and flame-retardant PVC drag chain cable material comprises the steps of mixing, extrusion, refining, granulation, screening, etc. The specific implementation process is as follows:

[0110] The preparation process of the mixed material is as follows:

[0111] Step 1: Add 8 parts of type B PVC resin and trimellitate into a high-speed mixer and stir for premixing at room temperature for 4 minutes, then mix at high speed for 5 minutes.

[0112] Step 2: Add type A PVC resin, 2050 polyester plasticizer and the remaining trimellitate into a high-speed mixer and mix for 5 minutes, and turn on the heating at the same time. When the heating temperature reaches 110°C, mix at a low speed for 2 minutes.

[0113] Step 3: Add antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, lubricant, inorganic silicate clay, and P551J processing modifier into a high-speed mixer and mix at high speed for 5 minutes.

[0114] Step 4: Add ethylene-vinyl acetate-maleic anhydride copolymer, P95 nitrile rubber, ethylene-vinyl acetate copolymer and polyester elastomer into a high-speed mixer, mix at a low speed for 2 minutes to obtain a mixture, and the mixing temperature is 130°C;

[0115] The extrusion preparation process is as follows:

[0116] The mixed material is added into a twin-screw extruder for extrusion to obtain an extrudate, the extrusion temperature is set at 140°C, and the screw speed frequency is 40 Hz;

[0117] The preparation process of the open refining is as follows:

[0118] The extrudate is added into an open mill for open milling to obtain an open mill material, and the open milling temperature is set to 170° C. The granulation preparation process is as follows:

[0119] The raw material was added into a single screw granulator for granulation to obtain granulated material, and the granulation temperature was set at 90°C;

[0120] The preparation process of the sieving is as follows:

[0121] The granulated material is cooled and then sieved, and the particle size of the sieved material is 3 mm, thus obtaining the high-strength and flame-retardant PVC drag chain cable material.

[0122] Comparative Example 1:

[0123] A high-strength and flame-retardant PVC drag chain cable material raw material includes type A PVC resin, type B PVC resin, trioctyl trimellitate, 2050 polyester plasticizer, antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, ethylene-vinyl acetate copolymer, lubricant, P551J processing modifier, ethylene-vinyl acetate-maleic anhydride copolymer, polyester elastomer, and inorganic silicate clay;

[0124] The dosage is measured by mass, including: 80 parts of type A PVC resin, 30 parts of type B PVC resin, 15 parts of trioctyl trimellitate, 17 parts of 2050 polyester plasticizer, 6 parts of antimony trioxide, 8 parts of zinc borate, 4-8 parts of filler, 12 parts of aluminum hydroxide, 10 parts of calcium zinc heat stabilizer, 12 parts of ethylene-vinyl acetate copolymer, 0.5 parts of lubricant, 0.8 parts of P551J processing modifier, 4 parts of ethylene-vinyl acetate-maleic anhydride copolymer, 15 parts of polyester elastomer, and 1.5 parts of inorganic silicate clay;

[0125] The polymerization degree of the type A PVC resin is 1200;

[0126] The B-type PVC resin has a degree of polymerization of 2500;

[0127] The vinyl acetate content in the ethylene-vinyl acetate copolymer is 30%;

[0128] The filler is selected from at least one of calcium carbonate, talc and kaolin;

[0129] The lubricant is selected from at least one of stearic acid, polyethylene wax, calcium stearate, and zinc stearate;

[0130] The ethylene-vinyl acetate-maleic anhydride copolymer is prepared by the following steps:

[0131] Step 1: Put ethylene-vinyl acetate copolymer and maleic anhydride into a high-speed mixer and stir for 30 minutes to mix them thoroughly;

[0132] Step 2: Put the mixed ethylene-vinyl acetate copolymer and maleic anhydride into the barrel of a twin-screw extruder for extrusion process at a temperature of 150°C, and add an initiator in the third heating zone;

[0133] The initiator content is 0.8 parts, and is prepared by mixing diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bishexane and antioxidant 1010 in a mass ratio of 1:1:1, and the mixing method is ball milling stirring, the speed is 250 rpm, and the time is 40 minutes;

[0134] Step 3: Granulate with a single screw granulator, and set the granulation temperature to 100°C;

[0135] Step 4: cooling and sieving to obtain the ethylene-vinyl acetate-maleic anhydride copolymer, the particle size of the sieved material is 0.6 mm;

[0136] A preparation method of a high-strength and flame-retardant PVC drag chain cable material comprises the steps of mixing, extrusion, refining, granulation, screening, etc. The specific implementation process is as follows:

[0137] The preparation process of the mixed material is as follows:

[0138] Step 1: Add 8 parts of type B PVC resin and trimellitate into a high-speed mixer and stir for premixing at room temperature for 4 minutes, then mix at high speed for 5 minutes.

[0139] Step 2: Add type A PVC resin, 2050 polyester plasticizer and the remaining trimellitate into a high-speed mixer and mix for 5 minutes, and turn on the heating at the same time. When the heating temperature reaches 110°C, mix at a low speed for 2 minutes.

[0140] Step 3: Add antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, lubricant, inorganic silicate clay, and P551J processing modifier into a high-speed mixer and mix at high speed for 5 minutes.

[0141] Step 4: Add ethylene-vinyl acetate-maleic anhydride copolymer, ethylene-vinyl acetate copolymer and polyester elastomer into a high-speed mixer, mix at a low speed for 2 minutes to obtain a mixture, and the mixing temperature is 130°C;

[0142] The extrusion preparation process is as follows:

[0143] The mixed material is added into a twin-screw extruder for extrusion to obtain an extrudate, the extrusion temperature is set at 140°C, and the screw speed frequency is 40 Hz;

[0144] The preparation process of the open refining is as follows:

[0145] The extrudate is added into an open mill for open milling to obtain an open mill material, and the open milling temperature is set to 170° C. The granulation preparation process is as follows:

[0146] The raw material was added into a single screw granulator for granulation to obtain granulated material, and the granulation temperature was set at 90°C;

[0147] The preparation process of the sieving is as follows:

[0148] The granulated material is cooled and then sieved, and the particle size of the sieved material is 3 mm, thus obtaining the high-strength and flame-retardant PVC drag chain cable material.

[0149] Comparative Example 2:

[0150] A high-strength and flame-retardant PVC drag chain cable material raw material includes type A PVC resin, type B PVC resin, trioctyl trimellitate, 2050 polyester plasticizer, antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, P95 nitrile rubber, lubricant, P551J processing modifier, ethylene-vinyl acetate-maleic anhydride copolymer, polyester elastomer, and inorganic silicate clay;

[0151] The dosage is measured by mass, including: 80 parts of type A PVC resin, 30 parts of type B PVC resin, 15 parts of trioctyl trimellitate, 17 parts of 2050 polyester plasticizer, 6 parts of antimony trioxide, 8 parts of zinc borate, 4-8 parts of filler, 12 parts of aluminum hydroxide, 10 parts of calcium zinc heat stabilizer, 13 parts of P95 nitrile rubber, 0.5 parts of lubricant, 0.8 parts of P551J processing modifier, 4 parts of ethylene-vinyl acetate-maleic anhydride copolymer, 15 parts of polyester elastomer, and 1.5 parts of inorganic silicate clay;

[0152] The polymerization degree of the type A PVC resin is 1200;

[0153] The B-type PVC resin has a degree of polymerization of 2500;

[0154] The filler is selected from at least one of calcium carbonate, talc and kaolin;

[0155] The lubricant is selected from at least one of stearic acid, polyethylene wax, calcium stearate, and zinc stearate;

[0156] The ethylene-vinyl acetate-maleic anhydride copolymer is prepared by the following steps:

[0157] Step 1: Put ethylene-vinyl acetate copolymer and maleic anhydride into a high-speed mixer and stir for 30 minutes to mix them thoroughly;

[0158] Step 2: Put the mixed ethylene-vinyl acetate copolymer and maleic anhydride into the barrel of a twin-screw extruder for extrusion process at a temperature of 150°C, and add an initiator in the third heating zone;

[0159] The initiator content is 0.8 parts, and is prepared by mixing diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bishexane and antioxidant 1010 in a mass ratio of 1:1:1, and the mixing method is ball milling stirring, the speed is 250 rpm, and the time is 40 minutes;

[0160] Step 3: Granulate with a single screw granulator, and set the granulation temperature to 100°C;

[0161] Step 4: cooling and sieving to obtain the ethylene-vinyl acetate-maleic anhydride copolymer, the particle size of the sieved material is 0.6 mm;

[0162] A preparation method of a high-strength and flame-retardant PVC drag chain cable material comprises the steps of mixing, extrusion, refining, granulation, screening, etc. The specific implementation process is as follows:

[0163] The preparation process of the mixed material is as follows:

[0164] Step 1: Add 8 parts of type B PVC resin and trimellitate into a high-speed mixer and stir for premixing at room temperature for 4 minutes, then mix at high speed for 5 minutes.

[0165] Step 2: Add type A PVC resin, 2050 polyester plasticizer and the remaining trimellitate into a high-speed mixer and mix for 5 minutes, and turn on the heating at the same time. When the heating temperature reaches 110°C, mix at a low speed for 2 minutes.

[0166] Step 3: Add antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, lubricant, inorganic silicate clay, and P551J processing modifier into a high-speed mixer and mix at high speed for 5 minutes.

[0167] Step 4: Add ethylene-vinyl acetate-maleic anhydride copolymer, P95 nitrile rubber and polyester elastomer into a high speed mixer and mix at low speed for 2 minutes to obtain a mixture at a mixing temperature of 130°C;

[0168] The extrusion preparation process is as follows:

[0169] The mixed material is added into a twin-screw extruder for extrusion to obtain an extrudate, the extrusion temperature is set at 140°C, and the screw speed frequency is 40 Hz;

[0170] The preparation process of the open refining is as follows:

[0171] The extrudate is added into an open mill for open milling to obtain an open mill material, and the open milling temperature is set to 170° C. The granulation preparation process is as follows:

[0172] The raw material was added into a single screw granulator for granulation to obtain granulated material, and the granulation temperature was set at 90°C;

[0173] The preparation process of the sieving is as follows:

[0174] The granulated material is cooled and then sieved, and the particle size of the sieved material is 3 mm, thus obtaining the high-strength and flame-retardant PVC drag chain cable material.

[0175] Comparative Example 3:

[0176] A high-strength and flame-retardant PVC drag chain cable material raw material includes type A PVC resin, type B PVC resin, trioctyl trimellitate, 2050 polyester plasticizer, antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, P95 nitrile rubber, ethylene-vinyl acetate copolymer, lubricant, P551J processing modifier, ethylene-vinyl acetate-maleic anhydride copolymer, polyester elastomer, and inorganic silicate clay;

[0177] The dosage is measured by mass, including: 80 parts of type A PVC resin, 30 parts of type B PVC resin, 15 parts of trioctyl trimellitate, 17 parts of 2050 polyester plasticizer, 6 parts of antimony trioxide, 8 parts of zinc borate, 4-8 parts of filler, 12 parts of aluminum hydroxide, 10 parts of calcium zinc heat stabilizer, 18 parts of P95 nitrile rubber, 12 parts of ethylene-vinyl acetate copolymer, 0.5 parts of lubricant, 0.8 parts of P551J processing modifier, 4 parts of ethylene-vinyl acetate-maleic anhydride copolymer, 15 parts of polyester elastomer, and 1.5 parts of inorganic silicate clay;

[0178] The polymerization degree of the type A PVC resin is 1200;

[0179] The B-type PVC resin has a degree of polymerization of 2500;

[0180] The vinyl acetate content in the ethylene-vinyl acetate copolymer is 30%;

[0181] The filler is selected from at least one of calcium carbonate, talc and kaolin;

[0182] The lubricant is selected from at least one of stearic acid, polyethylene wax, calcium stearate, and zinc stearate;

[0183] The ethylene-vinyl acetate-maleic anhydride copolymer is prepared by the following steps:

[0184] Step 1: Put ethylene-vinyl acetate copolymer and maleic anhydride into a high-speed mixer and stir for 30 minutes to mix them thoroughly;

[0185] Step 2: Put the mixed ethylene-vinyl acetate copolymer and maleic anhydride into the barrel of a twin-screw extruder for extrusion process at a temperature of 150°C, and add an initiator in the third heating zone;

[0186] The initiator content is 0.8 parts, and is prepared by mixing diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bishexane and antioxidant 1010 in a mass ratio of 1:1:1, and the mixing method is ball milling stirring, the speed is 250 rpm, and the time is 40 minutes;

[0187] Step 3: Granulate with a single screw granulator, and set the granulation temperature to 100°C;

[0188] Step 4: cooling and sieving to obtain the ethylene-vinyl acetate-maleic anhydride copolymer, the particle size of the sieved material is 0.6 mm;

[0189] A preparation method of a high-strength and flame-retardant PVC drag chain cable material comprises the steps of mixing, extrusion, refining, granulation, screening, etc. The specific implementation process is as follows:

[0190] The preparation process of the mixed material is as follows:

[0191] Step 1: Add 8 parts of type B PVC resin and trimellitate into a high-speed mixer and stir for premixing at room temperature for 4 minutes, then mix at high speed for 5 minutes.

[0192] Step 2: Add type A PVC resin, 2050 polyester plasticizer and the remaining trimellitate into a high-speed mixer and mix for 5 minutes, and turn on the heating at the same time. When the heating temperature reaches 110°C, mix at a low speed for 2 minutes.

[0193] Step 3: Add antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, lubricant, inorganic silicate clay, and P551J processing modifier into a high-speed mixer and mix at high speed for 5 minutes.

[0194] Step 4: Add ethylene-vinyl acetate-maleic anhydride copolymer, P95 nitrile rubber, ethylene-vinyl acetate copolymer and polyester elastomer into a high-speed mixer, mix at a low speed for 2 minutes to obtain a mixture, and the mixing temperature is 130°C;

[0195] The extrusion preparation process is as follows:

[0196] The mixed material is added into a twin-screw extruder for extrusion to obtain an extrudate, the extrusion temperature is set at 140°C, and the screw speed frequency is 40 Hz;

[0197] The preparation process of the open refining is as follows:

[0198] The extrudate is added into an open mill for open milling to obtain an open mill material, and the open milling temperature is set to 170° C. The granulation preparation process is as follows:

[0199] The raw material was added into a single screw granulator for granulation to obtain granulated material, and the granulation temperature was set at 90°C;

[0200] The preparation process of the sieving is as follows:

[0201] The granulated material is cooled and then sieved, and the particle size of the sieved material is 3 mm, thus obtaining the high-strength and flame-retardant PVC drag chain cable material.

[0202] Comparative Example 4:

[0203] A high-strength and flame-retardant PVC drag chain cable material raw material includes type A PVC resin, type B PVC resin, trioctyl trimellitate, 2050 polyester plasticizer, antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, P95 nitrile rubber, ethylene-vinyl acetate copolymer, lubricant, P551J processing modifier, ethylene-vinyl acetate-maleic anhydride copolymer, polyester elastomer, and inorganic silicate clay;

[0204] The dosage is measured by mass, including: 80 parts of type A PVC resin, 30 parts of type B PVC resin, 15 parts of trioctyl trimellitate, 17 parts of 2050 polyester plasticizer, 6 parts of antimony trioxide, 8 parts of zinc borate, 4-8 parts of filler, 12 parts of aluminum hydroxide, 10 parts of calcium zinc heat stabilizer, 13 parts of P95 nitrile rubber, 16 parts of ethylene-vinyl acetate copolymer, 0.5 parts of lubricant, 0.8 parts of P551J processing modifier, 4 parts of ethylene-vinyl acetate-maleic anhydride copolymer, 15 parts of polyester elastomer, and 1.5 parts of inorganic silicate clay;

[0205] The polymerization degree of the type A PVC resin is 1200;

[0206] The B-type PVC resin has a degree of polymerization of 2500;

[0207] The vinyl acetate content in the ethylene-vinyl acetate copolymer is 30%;

[0208] The filler is selected from at least one of calcium carbonate, talc and kaolin;

[0209] The lubricant is selected from at least one of stearic acid, polyethylene wax, calcium stearate, and zinc stearate;

[0210] The ethylene-vinyl acetate-maleic anhydride copolymer is prepared by the following steps:

[0211] Step 1: Put ethylene-vinyl acetate copolymer and maleic anhydride into a high-speed mixer and stir for 30 minutes to mix them thoroughly;

[0212] Step 2: Put the mixed ethylene-vinyl acetate copolymer and maleic anhydride into the barrel of a twin-screw extruder for extrusion process at a temperature of 150°C, and add an initiator in the third heating zone;

[0213] The initiator content is 0.8 parts, and is prepared by mixing diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bishexane and antioxidant 1010 in a mass ratio of 1:1:1, and the mixing method is ball milling stirring, the speed is 250 rpm, and the time is 40 minutes;

[0214] Step 3: Granulate with a single screw granulator, and set the granulation temperature to 100°C;

[0215] Step 4: cooling and sieving to obtain the ethylene-vinyl acetate-maleic anhydride copolymer, the particle size of the sieved material is 0.6 mm;

[0216] A preparation method of a high-strength and flame-retardant PVC drag chain cable material comprises the steps of mixing, extrusion, refining, granulation, screening, etc. The specific implementation process is as follows:

[0217] The preparation process of the mixed material is as follows:

[0218] Step 1: Add 8 parts of type B PVC resin and trimellitate into a high-speed mixer and stir for premixing at room temperature for 4 minutes, then mix at high speed for 5 minutes.

[0219] Step 2: Add type A PVC resin, 2050 polyester plasticizer and the remaining trimellitate into a high-speed mixer and mix for 5 minutes, and turn on the heating at the same time. When the heating temperature reaches 110°C, mix at a low speed for 2 minutes.

[0220] Step 3: Add antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, lubricant, inorganic silicate clay, and P551J processing modifier into a high-speed mixer and mix at high speed for 5 minutes.

[0221] Step 4: Add ethylene-vinyl acetate-maleic anhydride copolymer, P95 nitrile rubber, ethylene-vinyl acetate copolymer and polyester elastomer into a high-speed mixer, mix at a low speed for 2 minutes to obtain a mixture, and the mixing temperature is 130°C;

[0222] The extrusion preparation process is as follows:

[0223] The mixed material is added into a twin-screw extruder for extrusion to obtain an extrudate, the extrusion temperature is set at 140°C, and the screw speed frequency is 40 Hz;

[0224] The preparation process of the open refining is as follows:

[0225] The extrudate is added into an open mill for open milling to obtain an open mill material, and the open milling temperature is set to 170° C. The granulation preparation process is as follows:

[0226] The raw material was added into a single screw granulator for granulation to obtain granulated material, and the granulation temperature was set at 90°C;

[0227] The preparation process of the sieving is as follows:

[0228] The granulated material is cooled and then sieved, and the particle size of the sieved material is 3 mm, thus obtaining the high-strength and flame-retardant PVC drag chain cable material.

[0229] Comparative Example 5:

[0230] A high-strength and flame-retardant PVC drag chain cable material raw material includes type A PVC resin, type B PVC resin, trioctyl trimellitate, 2050 polyester plasticizer, antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, P95 nitrile rubber, ethylene-vinyl acetate copolymer, lubricant, P551J processing modifier, ethylene-vinyl acetate-maleic anhydride copolymer, polyester elastomer, and inorganic silicate clay;

[0231] The dosage is measured by mass, including: 80 parts of type A PVC resin, 30 parts of type B PVC resin, 15 parts of trioctyl trimellitate, 17 parts of 2050 polyester plasticizer, 6 parts of antimony trioxide, 8 parts of zinc borate, 4-8 parts of filler, 12 parts of aluminum hydroxide, 10 parts of calcium zinc heat stabilizer, 13 parts of P95 nitrile rubber, 12 parts of ethylene-vinyl acetate copolymer, 0.5 parts of lubricant, 0.8 parts of P551J processing modifier, 15 parts of polyester elastomer, and 1.5 parts of inorganic silicate clay;

[0232] The polymerization degree of the type A PVC resin is 1200;

[0233] The B-type PVC resin has a degree of polymerization of 2500;

[0234] The vinyl acetate content in the ethylene-vinyl acetate copolymer is 30%;

[0235] The filler is selected from at least one of calcium carbonate, talc and kaolin;

[0236] The lubricant is selected from at least one of stearic acid, polyethylene wax, calcium stearate, and zinc stearate;

[0237] A preparation method of a high-strength and flame-retardant PVC drag chain cable material comprises the steps of mixing, extrusion, refining, granulation, screening, etc. The specific implementation process is as follows:

[0238] The preparation process of the mixed material is as follows:

[0239] Step 1: Add 8 parts of type B PVC resin and trimellitate into a high-speed mixer and stir for premixing at room temperature for 4 minutes, then mix at high speed for 5 minutes.

[0240] Step 2: Add type A PVC resin, 2050 polyester plasticizer and the remaining trimellitate into a high-speed mixer and mix for 5 minutes, and turn on the heating at the same time. When the heating temperature reaches 110°C, mix at a low speed for 2 minutes.

[0241] Step 3: Add antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, lubricant, inorganic silicate clay, and P551J processing modifier into a high-speed mixer and mix at high speed for 5 minutes.

[0242] Step 4: Add P95 nitrile rubber, ethylene-vinyl acetate copolymer and polyester elastomer into a high-speed mixer and mix at a low speed for 2 minutes to obtain a mixture at a mixing temperature of 130°C;

[0243] The extrusion preparation process is as follows:

[0244] The mixed material is added into a twin-screw extruder for extrusion to obtain an extrudate, the extrusion temperature is set at 140°C, and the screw speed frequency is 40 Hz;

[0245] The preparation process of the open refining is as follows:

[0246] The extrudate is added into an open mill for open milling to obtain an open mill material, and the open milling temperature is set to 170° C. The granulation preparation process is as follows:

[0247] The raw material was added into a single screw granulator for granulation to obtain granulated material, and the granulation temperature was set at 90°C;

[0248] The preparation process of the sieving is as follows:

[0249] The granulated material is cooled and then sieved, and the particle size of the sieved material is 3 mm, thus obtaining the high-strength and flame-retardant PVC drag chain cable material.

[0250] Tensile strength test:

[0251] Tensile strength is the resistance to the maximum uniform plastic deformation of the material. Before the tensile specimen is subjected to the maximum tensile stress, the deformation is uniform and consistent, but after exceeding the maximum tensile stress, the metal begins to shrink, that is, concentrated deformation occurs; for brittle materials with no (or very small) uniform plastic deformation, it reflects the fracture resistance of the material. The test standard can refer to the national standard GB / T228-1987, and the unit is MPa;

[0252] Elongation after break:

[0253] Refers to the percentage of the elongated length of the specimen to the original length when the material is broken by external force (tension). The test standard can refer to the national standard GB / T 528-2009;

[0254] Oxygen index test:

[0255] Oxygen index (OI) refers to the minimum oxygen concentration required for a material to burn with flame in an oxygen-nitrogen mixed gas flow under specified conditions. It is expressed as the volume percentage of oxygen. A high oxygen index indicates that the material is not easy to burn, and a low oxygen index indicates that the material is easy to burn. The test standard can refer to the national standard GB / T 2406.2-2009;

[0256] Volume resistivity test:

[0257] Volume resistivity is the resistance of a material to electric current per unit volume, and is used to characterize the electrical properties of a material. Generally, the higher the volume resistivity, the higher the efficiency of the material as an electrical insulating component. The test standard can refer to the national standard GB / T 22042-2008;

[0258] The test results are shown in Table 1:

[0259] Table 1: Performance Test

[0260]

[0261]

[0262] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution, which should be included in the scope of the claims of the present invention.

Claims

1. A high-strength and flame-retardant PVC drag chain cable material raw material includes type A PVC resin, type B PVC resin, trioctyl trimellitate, 2050 polyester plasticizer, antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, P95 nitrile rubber, ethylene-vinyl acetate copolymer, lubricant, P551J processing modifier, ethylene-vinyl acetate-maleic anhydride copolymer, polyester elastomer, and inorganic silicate clay.

2. The preparation method according to claim 1, characterized in that: The PVC drag chain cable material is measured by mass, wherein: 50-100 parts of type A PVC resin, 10-50 parts of type B PVC resin, 10-20 parts of trioctyl trimellitate, 15-20 parts of 2050 polyester plasticizer, 4-8 parts of antimony trioxide, 6-10 parts of zinc borate, 4-8 parts of filler, 8-16 parts of aluminum hydroxide, 8-12 parts of calcium zinc heat stabilizer, 10-15 parts of P95 nitrile rubber, 10-15 parts of ethylene-vinyl acetate copolymer, 0.4-0.6 parts of lubricant, 0.4-1 parts of P551J processing modifier, 3-5 parts of ethylene-vinyl acetate-maleic anhydride copolymer, 10-20 parts of polyester elastomer, and 1-2 parts of inorganic silicate clay.

3. The preparation method according to claim 1, characterized in that: The polymerization degree of the type A PVC resin is 1000-1500; The B-type PVC resin has a degree of polymerization of 2000-3000; The vinyl acetate content in the ethylene-vinyl acetate copolymer is 25-35%; The filler is selected from at least one of calcium carbonate, talc and kaolin; The lubricant is selected from at least one of stearic acid, polyethylene wax, calcium stearate and zinc stearate.

4. The preparation method according to claim 1, characterized in that: The ethylene-vinyl acetate-maleic anhydride copolymer is prepared by the following steps, including: Step 1: Place ethylene-vinyl acetate copolymer and maleic anhydride into a high-speed mixer and stir for 20-40 minutes to mix thoroughly; Step 2: Put the mixed ethylene-vinyl acetate copolymer and maleic anhydride into the barrel of a twin-screw extruder for extrusion process at an extrusion temperature of 140-160°C, and add an initiator in the third heating zone; Step 3: Use a single screw granulator to granulate, and set the granulation temperature to 90-110℃; Step 4: Cooling and sieving to obtain the ethylene-vinyl acetate-maleic anhydride copolymer, the particle size of the sieved material is 0.5-0.8 mm.

5. The preparation method according to claim 4, characterized in that: The initiator content is 0.5-1 part, and is prepared by mixing diisopropylbenzene peroxide, 2,5-dimethyl-2,5-bishexane and antioxidant 1010 in a mass ratio of 1:0.8-1.2:0.8-1.2, with a mixing method of ball milling, a rotation speed of 200-300 rpm, and a time of 30-60 minutes.

6. A high-strength and flame-retardant PVC drag chain cable material and a preparation method thereof, characterized in that: The process includes mixing, extruding, refining, granulating, screening and other steps.

7. The preparation method according to claim 6, characterized in that: The mixed material preparation method comprises: Step 1: Add 5-10 parts of type B PVC resin and trimellitate into a high-speed mixer and pre-mix for 2-5 minutes at room temperature, then mix at high speed for 3-7 minutes. Step 2: Add type A PVC resin, 2050 polyester plasticizer and the remaining trimellitate into a high-speed mixer and mix for 3-7 minutes, and turn on the heating at the same time. When the heating temperature reaches 100-120℃, mix at a low speed for 1-3 minutes. Step 3: Add antimony trioxide, zinc borate, filler, aluminum hydroxide, calcium zinc heat stabilizer, lubricant, inorganic silicate clay, and P551J processing modifier into a high-speed mixer and mix at high speed for 3-7 minutes. Step 4: Add ethylene-vinyl acetate-maleic anhydride copolymer, P95 nitrile rubber, ethylene-vinyl acetate copolymer and polyester elastomer into a high speed mixer, mix at a low speed for 1-3 minutes to obtain a mixture, and the mixing temperature is 130-140°C.

8. The preparation method according to claim 6, characterized in that: The extrusion preparation method comprises: The mixed material is added into a twin-screw extruder for extrusion to obtain an extruded material. The extrusion temperature is set at 130-150° C. and the screw speed frequency is 30-50 Hz.

9. The preparation method according to claim 6, characterized in that: The preparation method of the open refining comprises: The extrudate is added into an open mill for open mixing to obtain an open mixing material, and the open mixing temperature is set at 160-180°C.

10. The preparation method according to claim 4, characterized in that: The granulation preparation method comprises: The raw material is added into a single screw granulator for granulation to obtain granulated material, and the granulation temperature is set at 80-110°C.

Citation Information

Cited By

  • High-temperature-resistant flame-retardant PVC cable material and preparation method thereof

    CN120484406A